Optimized electrolyzer operation: Employing forecasts of wind energy availability, hydrogen demand, and electricity prices. (15th February 2019) - Grüger, F.; Hoch, O.; Hartmann, J.; Robinius, M.; Stolten, D.
Abstract: One of the main advantages of fuel cell based mobility over other sustainable mobility concepts is the flexible production of hydrogen via electrolysis. To date, it is unclear how electrolysis at hydrogen refueling stations should be operated in order to achieve the lowest possible costs despite the constraints of hydrogen demand. This study proposes and evaluates an intelligent operating strategy for electrolysis capable of exploiting times of low electricity prices while participating in the spot market and maximizing wind energy utilization when combined with a wind farm. This strategy is based on a simulation model considering imperfect forecasts (e.g. of wind availability or energy prices) and non-linear electrolyzer behavior. Results show that this approach reduces hydrogen production costs by up to 9.2% and increases wind energy utilization by up to 19%, respectively. Highlights: Electrolysis can be operated flexibly and complement renewables. Operating strategies of electrolysis should take forecasts into account. Predictive operation is most effective in combination with renewables. The presented strategy reduces hydrogen production costs by up to 9%. The presented strategy increases wind energy utilization by 19%.